Pulsed laser ablation as a tool for in-situ balancing of rotating parts - Stoesslein, M.; Axinte, Dragos A.; Bilbao Guillerna, A. (Elsevier, 2016)
The balancing of complex rotating systems is a challenging task as it may require repetitive (dis)assembly to enable mass adjustments; thus, developing methods for in-situ dynamic balancing of rotatives is regarded as a key technology enabler. In this context laser balancing with its high flexibility in adjusting its firing frequency (to match that of the rotating part) and pulse energy (to vary the material removal) could offer significant advantages from both precision and cost point of view.